Quality classification affects firmness of ground beef patties from the chuck roll - Emily C. Pownall; Robert S. McEwan; John A. Unruh; Sally L. Stroda (Kansas Agricultural Experiment Station Research Reports, 2014)
Consumers often use color as the main criteria in selecting meat products, and they associate a bright red color with freshness. Longer display life without discoloration can result in more opportunities to sell the product and greater potential for profit. Flavor, juiciness, and tenderness are also associated with consumer satisfaction. Although grinding offers an opportunity to mechanically minimize differences in tenderness, product quality can affect these sensory properties of ground beef. The objective of this study was to determine the effects of three quality classifications and their combinations on ground beef patty display color stability and sensory attributes evaluated by a trained sensory panel and consumer panel.
Keywords: Cattlemen' s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen' s Day; Beef; Ground beef; Subprimals; Color; Consumer satisfaction; Sensory attributes